Beliefs and barriers associated with COVID-19 vaccination among the general population in Saudi Arabia - Rania M. Magadmi; Fatemah O. Kamel (BMC, 2021)
Abstract Background Developing a vaccine against COVID-19 is considered a key strategy to end the pandemic. However, public acceptance is reliant on beliefs and perception toward the vaccine. Therefore, the study aimed to assess the beliefs and barriers associated with COVID-19 vaccination among the Saudi population. Methods An online self-administered questionnaire was distributed across the main regions of Saudi Arabia on May 2020. The questionnaire addressed the socio-demographic variables, beliefs toward COVID-19 vaccination, and potential barriers that may prevent participants from being vaccinated. The association between COVID-19 vaccine acceptance and sociodemographic variables were analyzed. Logistic regression analysis was used to identify the predicting variables of vaccine acceptance. Results Out of 3101 participants, 44.7% were accepting of COVID-19 vaccination if available, whereas 55.3% admitted hesitancy. Younger, male, who received seasonal influenza vaccine were more likely to accept taking the vaccine. The study found that concerns about side effects were the key barrier for vaccine acceptance. Furthermore, the majority of refusers may accept the vaccine if additional studies confirmed safety and effectiveness. Conclusion Results can be utilized in planning vaccination campaigns while waiting for vaccine development.